Synthesis, characterization, and investigation photophysicochemical properties of axially 2-hydroxymethyl-1,4-b enzodioxan di-substitute d Silicon(IV) phthalocyanine - Kayir, Nisa; Gorduk, Semih (ELSEVIER SCIENCE SA, 2023)
Phthalocyanines are a derivative of macro heterocyclic compound and the different substituents can be added to phthalocyanine ring according to aim. Thus, they can be used in many industrial and scientific areas. One of these important areas is photodynamic therapy (PDT) treatment of cancer. In this study; Silicon(IV) phthalocyanine was preferred because it easily undergoes chemical modi-fication thanks to its axial position and 2-hydroxymethyl-1,4-benzodioxan was used as a substituent to provide solubility in organic solvents thanks to its alkyl and oxygen groups. As a result, a new compound was synthesized with Silicon(IV) as the central metal atom and a soluble substituent in the axial posi-tion. The molecular structure of this newly synthesized substance was characterized by UV-Vis, FT-IR, MALDI TOF MS, and 1 H NMR. The substance's photophysical and photochemical characteristics were in-vestigated in both DMSO and DMF solvents. Additionally, singlet oxygen quantum yields were calculated as OA: 0.65 in DMSO and OA: 0.69 in DMF and this new compound produced significant singlet oxygen quantum yields, making it potentially useful as a photosensitizer in photodynamic treatment (PDT) for cancer. (c) 2023 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Photodynamic therapy; Silicon(IV) Axial; 2-hydroxymethyl-1; 4-benzodioxan; THERAPY; Chemistry